A coach's responsibility: learning how to prepare athletes for peak performance - Johnson, S. R.; Wojnar, P. J.; Price, W. J.; Foley, T. J.; Moon, J. R.; Esposito, E. N.; Cromartie, F. J. (The Sport Journal, 2011)
Abstract The coaching profession is ever-changing and coaches at each level of sport competition need to know more than just the Xs and Os in order to be successful. As the primary individuals tasked with developing athletes and helping them achieve their goals, coaches should acquire a working knowledge of all areas affiliated with performance enhancement. Specifically, the disciplines of sports administration, sports medicine, strength and conditioning, and sports psychology can assist coaches while physically and mentally training their athletes. This article illustrates six primary components of these disciplines: risk management, injury prevention, communication, nutrition, goal setting, and athlete development. It is imperative coaches gain a familiarity with these aforementioned components in order to teach athletes about skill development and prepare them to achieve peak performance.